1985
DOI: 10.1152/jappl.1985.59.4.1258
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of brief baroreceptor stimuli in the anesthetized dog

Abstract: To quantify the immediate isocapnic respiratory response to baroreceptor stimulation, pressure in the isolated externally perfused carotid sinuses (CS) of 24 vagotomized alpha-chloralose-anesthetized dogs was increased selectively during either inspiration or expiration as a step (from time of onset to end of respiratory phase) or a pulse (500 ms). The rise time (150 ms), base-line pressure (80 mmHg), and stimulus magnitude (40 mmHg) were similar for the two stimuli. The time of stimulus onset (delay), express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…In their study, the authors showed convincing examples of both effects and noted that tidal volume was not significantly affected. Similar findings in the dog have been reported by other groups (Brunner et al 1982; Dove et al 1985). In contrast, using the same approach, Maass-Moreno and Katona lengthened TE but shortened TI in the cat (Maass-Moreno et al 1989).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In their study, the authors showed convincing examples of both effects and noted that tidal volume was not significantly affected. Similar findings in the dog have been reported by other groups (Brunner et al 1982; Dove et al 1985). In contrast, using the same approach, Maass-Moreno and Katona lengthened TE but shortened TI in the cat (Maass-Moreno et al 1989).…”
Section: Discussionsupporting
confidence: 92%
“…Such effects may underlie the variability of respiratory responses (particularly pertaining to TI) reported in the literature. Baroreceptor activation has been reported to have bradypneic (Brunner et al 1982; Dove et al 1985) or no effects (Grunstein et al 1975; Miserocchi et al 1980) on respiratory frequency, and to either lengthen (Brunner et al 1982; Dove et al 1985) or shorten TI (Maass-Moreno et al 1989). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data provide a neural substrate for the expiratory– facilitatory response to activation of baroreceptors (Brunner et al, 1982; Dove and Katona, 1985; Grunstein et al, 1975; Li et al, 1999a,b; Lindsey et al, 1998; Nishino and Honda, 1982; Richter and Seller, 1975; Speck and Webber, 1983; Stella et al, 2001). We clearly demonstrate that barostimulation activates post-I neurones and depresses aug-E neurones.…”
Section: Discussionmentioning
confidence: 76%
“…The unified model defines a neural substrate for the expiratory-facilitatory response to activation of baroreceptors (Brunner et al, 1982; Dove and Katona, 1985; Grunstein et al, 1975; Li et al, 1999a,b; Lindsey et al, 1998; Nishino and Honda, 1982; Richter and Seller, 1975; Speck and Webber, 1983; Stella et al, 2001) and explains previous experimental findings that respiratory neurons, preferentially expiratory neurons, are modulated with the arterial pulse (Dick and Morris, 2004; Dick et al, 2005). This substrate can be used for further extending the model to incorporate interactions with the parasympathetic nervous system, since baroactivated post-I neurons were also found to be crucially involved in the modulation of cardiac vagal motoneurons (Gilbey et al, 1984).…”
Section: Unified Theoretical Framework For Respiratory–sympathetic mentioning
confidence: 75%